Pengaruh Independensi, Pengalaman, Due Professional Care, Akuntabilitas, dan kompetensi Terhadap Kualitas AuditStudi pada Kantor Akuntan Publik di Surakarta dan Semarang) - Rahayu, Nita Timur (2017)
This research aim to know influence of independency, experience, due professional care, accountability, and interest to audit quality. Population in this research is laboring auditor at Public Accountant Office in Surakarta and Semarang. Method gathering of sample by using technique of purposive sampling. Sample which used in this research amount to 43 espondents. In this research to data analyze use double regresssion analysis. Result of the research indicate that R 2 obtained value 0,790 meaning that 79,0% quality of audit influenced by independency, experience, due professional care, accountability, and interest. The rest counted 21,0% influenced by variable outside model. Result of t test indicate that job experience, due professional care, interest have an effect on to audit quality. While and independency of accountability do not have an effect on to audit quality.